Odpowiedzi

  • Użytkownik Zadane
2010-03-04T22:30:34+01:00
{2x-y=-1/*2
{3x+2y=9

4x-2y=-2
3x+2y=9

7x=7/7
x=1



{2y-x=8/*(-3)
{4x+3y=1/*2


3x-6y=24
8x+6y=2

11x=26/11
x=2 i 4/11


{3x-8y=8
{2x-y=1/*(-8)

3x-8y=8
-16x+8y=-8

-13x=0
x=0

{2x+3y=20
{-x+3y=-1/*(-1)



2x+3y=20
x-3y=1
3x=21/3
x=7
1 1 1
2010-03-04T22:37:32+01:00
2x-y=-1/*2
3x+2y=9
4x-2y=-2
3x+2y=9
7x=7
x=7
14-y=-1
15=y

2y-x=8/*4
4x+3y=1
8y-4x=32
4x+3y=1
11y=33
y=3
6-x=8
x=-2

3x-8y=8/*(-2)
2x-y=1/*3
-6x+16y=-16
6x-3y=3
13y=-13
y=-1
2x+1=1
x=0

2x+3y=20
-x+3y=-1/*2
2x+3y=20
-2x+6y=-2
9y=18
y=2
2x+6=20
x=7

1 3 1